Revisiting the hospital-issued gown in hospitalizations from a locus of control and patient-centered care perspectives: a call for design thinking - Gillie Gabay; Hana Ornoy (Frontiers Media S.A., 2024)
IntroductionPatient-centered care (PCC) is the preferred health policy approach that emphasizes responding to individual patient preferences, wishes, and needs. PCC requires active patient engagement. While there has been extensive research on physicians' robes, there is limited research on hospital-issued patient gowns during hospitalizations. How does the gown affect the cognitive-emotional experience of hospitalized patients? How is the gown associated with PCC?MethodsThe sample of this cross-sectional study consisted of 965 patients who were hospitalized at least once during the past year in a tertiary hospital. Measures were previously published.ResultsThe gown was strongly associated with lack of control and increased distress, and was negatively associated with patient proactiveness, engagement, and taking responsibility for self-management of chronic illness. Compared to male patients, female patients wearing the gown had stronger negative emotions and cognitively strong associations with the external locus of control, which inhibited engagement.DiscussionThe hospital gown is an unacknowledged barrier to achieving PCC, inhibits patient engagement, and reflects the paradoxes of inadvertently excluding patients' needs from hospital practice. The hospital gown must be modified to protect the patient's voice and enhance engagement. Policymakers are called to apply design thinking to facilitate patient participation in decision-making to accord hospital clothing to PCC and improve healthcare delivery.